New Section and New species of a bluing Psilocybe (Fungi, Basidiomycotina, Agaricales) from Colombia (2007)
ABSTRACT: Psilocybe bispora is described as a new caerulescent species from Antioquia, Colombia. The species is characterized by having two types of basidiospores: subrhomboid thickwalled, and subellipsoid thin-walled, when observed in face-view. Psilocybe bispora belongs to a new section of the genus, section Bisporae, here described. Both the species and the section belong to the hallucinogenic mushrooms of the genus because of the bluing feature of the basidioma